Investigation of thermal properties of gadolinium doped carbon nanotubes - Abaszade, R.G.; Aliyev, E.M.; Mammadov, A.G.; Khanmamadova, E.A.; Guliyev, A.A.; Aliyev, F.G.; Zapukhlyak, R.I.; Budak, H.F.; Kasapoglu, A.E.; Margitych, T.O.; et al. (Physics and Chemistry of Solid State, 2024)
Thermal properties characterizations for 10% and 15% Gd doped multi wall carbon nanotubes (MWCNTs) were investigated. TGA/DSC and TEM techniques were used for characterization. The features of mass loss characteristics for synthesized nanocomposite carbon nanomaterials were investigated. The specific heat capacities of the samples at a constant pressure increased as the temperature increased.